CEMARAN PESTISIDA KLOR-ORGANIK PADA SEDIMEN DANAU BUYAN BULELENG BALI - Ida Bagus Putra Manuaba (Bumi Lestari Journal of Environment)
This is an expost facto study with Analytical Cross Sectional Study design, within twostep activities, i.e. field study in order to gain sampling zone and obtaining sample needed.Followed by laboratory works in order to obtain pesticide residual contamination on water.Sample preparation for this purposed was carried out following a standard method. Gaschromatography was employed in order to gain the pesticide contaminant.Positive organochlorine pesticide contaminant, i.e. DDT and chlorotalonile wereobserved from 55 sampling point of sediment taken from 5 sampling zone. DDT in thesediment is 13.6 ppb with still bellow the maximum level of 42 ppb. Chlorotalonile insediment is 12.3 ppb. There is no threshold value of chlorotalonile, however, thiscontamination still bellow the RfD 15 ppb and ADI 30 ppb (PIP, 1995; Caroline, 1997).